International sectoral spillovers: An empircal analysis for German and US Industries - Werner Smolny (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1995)
In the paper, productivity convergence is analyzed with a broad panel of industry sector data for the United States and Germany for 1960-1990. The time-series/cross-sectoral data set allows to investigate country-specific convergence, and to control for sector-specific differences in human capital and factorutilization. It is found that the technological distance had a significant effect on German sectoral productivity growth in the sixties and seventies. Some part of the catching-up is due to capital-deepening, but most of it is total factor productivity convergence, i.e. endogenous growth models relying on knowledge spillovers receive support by the estimates. In addition, being behind had a significant impact on sectoral prices and employment in Germany.
Keywords: C33; D24; O47; O57; 330; Endogenous growth; sectoral spillovers; convergence; Produktivität; Industrie; Entwicklungskonvergenz; Spillover-Effekt; Neue Wachstumstheorie; Deutschland; USA